Historical Tourism from a Cultural Studies Perspective : Study of the Tjilik Riwut Hermitage Site, Katingan Regency - Husni, Muhammad (Journal of Islamic History, 2024)
This research is a cultural research on the activities of people who make tourist visits to historical sites, researchers are interested in revealing the motivations of tourists visiting the historical sites of Bukit Batu. The existence of the Bukit Batu site visited by tourists and pilgrims has a legendary background story filled with myths that gave birth to local culture, making it unique to study. Several previous studies examined the phenomenon of religious tourism traditions surrounding tomb pilgrimages and other mystical traditions of places, what distinguishes this research is that the object of pilgrims visiting this site is multi-religious, therefore researchers will examine it from a cultural perspective. Based on the observation of the socio-cultural reality of the community at the location, this study used descriptive qualitative methods with data collection techniques based on observations and in-depth interviews with tourists and tour guides as informants. Based on the results of observations and interviews, it was found that some of the motivations of tourists visiting the first historical site, visitors to travel in this case enjoy the scenery in the site environment. Second, visitors who come have the intention of taking blessings in the form of asking for something related to material and non-material things to the supernatural rulers who are believed to be residing at the site. Third, visitors who come with the intention of paying their vows or promises after their requests to the supernatural are granted by including offerings as a medium of gratitude.